DIGITAL HERMENEUTICS OF THE QUR’AN : TANTANGAN TASFIR DI ERA ARTIFICIAL INTELLIGENCE - Aulia, Nizam Udin (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2025)
The rapid development of Artificial Intelligence (AI) has significantly transformed how people interact with information, including in the field of Islamic studies and Qur’anic interpretation. Today, technologies such as Natural Language Processing (NLP), machine learning algorithms, and digital platforms are increasingly being used to read, analyze, and even "interpret" verses of the Qur’an automatically. This phenomenon raises deep questions about interpretive authority, the validity of digital exegesis, and whether the sacred meaning of the Qur’an is at risk of being reduced—or potentially enriched—by technological mediation. In this context, digital hermeneutics emerges as a contemporary approach that seeks to address these challenges while bridging classical interpretive traditions with modern interpretive needs in a digital age. This paper explores both the challenges and opportunities presented by the use of AI in Qur’anic studies, emphasizing the importance of maintaining ethical considerations and scholarly integrity in the face of automated meaning production. Digital hermeneutics is not intended to replace traditional methods of tafsir but to complement them. When approached critically and responsibly, it can help expand access, enrich perspectives, and offer new ways for Muslims to engage with the Qur’an in the modern world. However, it must remain grounded in rigorous methodology and the ethical values of Islamic scholarship to ensure that technology serves as a tool for deeper understanding rather than superficial interpretation. Keywords: Digital Hermeneutics, Qur’anic Exegesis, Artificial Intelligence (AI), Interpretive Ethics